2018
DOI: 10.4049/jimmunol.1701256
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the IL-33/IL-13 Axis in Obesity by IL-13Rα2

Abstract: In obesity, IL-13 overcomes insulin resistance by promoting anti-inflammatory macrophage differentiation in adipose tissue. Endogenous IL-13 levels can be modulated by the IL-13 decoy receptor, IL-13Rα2, which inactivates and depletes the cytokine. In this study, we show that IL-13Rα2 is markedly elevated in adipose tissues of obese mice. Mice deficient in IL-13Rα2 had high expression of IL-13 response markers in adipose tissue, consistent with increased IL-13 activity at baseline. Moreover, exposure to the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…Several studies have utilized IL-33 to increase ILC2s, eosinophils, and/or M2-like macrophages in WAT, often associated with weight loss and improved glucose control [31,94,106,112,115,117,119]. However, one group noted that IL-33 administration resulted in diarrhea and reduced food intake [106], either of which could induce weight loss (and subsequent metabolic benefits) independent of modulating WAT immune cell populations. This is an example of a complication that all metabolic and weight studies attempt to avoid in order to conclusively assume the improved metabolic readouts of the study are due to the proposed biological mechanism and not an unintended off-target induction of weight loss.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have utilized IL-33 to increase ILC2s, eosinophils, and/or M2-like macrophages in WAT, often associated with weight loss and improved glucose control [31,94,106,112,115,117,119]. However, one group noted that IL-33 administration resulted in diarrhea and reduced food intake [106], either of which could induce weight loss (and subsequent metabolic benefits) independent of modulating WAT immune cell populations. This is an example of a complication that all metabolic and weight studies attempt to avoid in order to conclusively assume the improved metabolic readouts of the study are due to the proposed biological mechanism and not an unintended off-target induction of weight loss.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In our own studies, we found that despite specifically elevating numbers of WAT eosinophils in obese mice with either recombinant IL-5 (rIL-5) treatment or using CCR2 deficient mice, there was no improvement in glucose tolerance [72,110,123]. Several studies have utilized IL-33 to increase ILC2s, eosinophils, and/or M2-like macrophages in WAT, often associated with weight loss and improved glucose control [31,94,106,112,115,117,119]. However, one group noted that IL-33 administration resulted in diarrhea and reduced food intake [106], either of which could induce weight loss (and subsequent metabolic benefits) independent of modulating WAT immune cell populations.…”
Section: Downloaded Frommentioning
confidence: 99%
“…A more recent study shows that, along with IL‐13Rα1, the IL‐13 decoy receptor IL‐13Rα2 is also upregulated in WAT of mice placed on HFD . The authors hypothesize that increased expression of IL‐13Rα2 reduces IL‐13 levels in WAT of obese mice, thereby promoting obesity.…”
Section: Tissue‐specific Effector Function Of Ilc2smentioning
confidence: 99%
“…The authors hypothesize that increased expression of IL‐13Rα2 reduces IL‐13 levels in WAT of obese mice, thereby promoting obesity. While mice lacking IL‐13Rα2 respond to HFD like control mice do, additional treatment with IL‐33 leads them to have more pronounced weight loss and decreased blood glucose levels . However, IL‐13Rα2‐deficient mice on HFD treated with IL‐33 also develop more diarrhea, thus, making it difficult to attribute the weight loss specifically to metabolic changes in response to IL‐13Rα2 deficiency .…”
Section: Tissue‐specific Effector Function Of Ilc2smentioning
confidence: 99%
“…IL-13 [100] and LTE 4 [101] elicit mucin release from goblet cells. IL-13 is induced in the adipose tissue of obese humans and activates IL-13Rα2 on adipocytes [102]. Histamine [103] and osteopontin [104] activate H 1 and osteopontin receptor on osteoblasts and osteoclasts, respectively.…”
Section: Mast Cells In the Homeostasis Of The Immune Systemmentioning
confidence: 99%